Repatriation of Patients to Referral Centers and Outcomes After Kidney Transplantation: A Single-center Analysis From the United Kingdom. Issue 11 (November 2018) - Khalil, Khalid; Hodson, James; Anderson, Benjamin; Nath, Jay; Sharif, Adnan
Abstract : Background: The aim of this study was to compare posttransplant outcomes of kidney allograft recipients between those followed up at transplant centers and those that were repatriated back to referral renal units. Methods: We analyzed data for 1375 consecutive patients transplanted in a single center in the United Kingdom. Patients were stratified into 3 groups: (1) externally referred patients with repatriation back for external follow-up (repatriated, n = 463), (2) externally referred patients not repatriated and followed-up internally at transplant center (nonrepatriated, n = 365), and (3) internally referred patients within transplant center with continued internal transplant center follow-up (internal, n = 547). Patient and death-censored graft survival were compared between groups on both univariable and multivariable analyses. Results: Baseline comparisons found that the nonrepatriated group had increased risk for prolonged length of stay and delayed graft function compared with repatriated patients. The nonrepatriated group had significantly shorter survival compared to the repatriated patients (90.2% vs 94.1% at 5 years, P = 0.013), which persisted after adjustment for confounders on multivariable analysis (hazard ratio, 1.86; 95% confidence interval, 1.06-3.28; P = 0.032). Death-censored graft survival was not found to differ significantly between the 3 groups ( P = 0.192). Conclusions: Our results provide reassurance regarding repatriation of care after kidney transplantation for the United Kingdom. Nonrepatriated patients are identified as a high-risk group for increased mortality, but further investigation is warranted to probe this heterogeneous group and validate in a non-United Kingdom cohort.